Pengaruh Kepemimpinan Dan Motivasi Ekstrinsik Terhadap Kinerja Karyawan: Studi Kasus Pada Salah Satu Restoran Di Bandung - Pri Widiastuti; Bulan Tati Fitria; Retno Resawati; Kadir Kadir (Acman: Accounting and Management Journal, 2022)
Researchers researched to know the effect of leadership and extrinsic motivation on employee performance at a restaurant in Bandung. Moreover, this research analyzes the factors that have the most dominant influence between leadership and extrinsic motivation on employee performance at a restaurant in Bandung, which are the object of research of as many as 46 employees using a questionnaire. Based on research using path analysis, the variables of leadership and extrinsic motivation on employee performance at a restaurant in Bandung are declared valid. Therefore, the conclusions and considerations related to the research results are paying attention to leadership and extrinsic motivation to improve employee performance. The results of the study show that leadership (X1) has a significant influence on employee performance (Y). then Extrinsic Motivation (X2) significantly influences Employee Performance (Y). Therefore, leadership (X1) and Extrinsic Motivation (X2) have a significant influence on Employee Performance (Y). To create a high leadership influence on employee performance, companies should pay more attention to the dimensions of the leadership variable so that employees are motivated and feel responsible and play an important role so that they can improve performance in quality and quantity. Furthermore, in connection with the strong influence of extrinsic motivation on employee performance, it is necessary to increase and improve the factors that make employee morale improving performance increase, for example, the salary factor for employees so that employees feel they have to increase the quality and quantity of their work in return for the rights they have. Get. To create a powerful influence of leadership and extrinsic motivation on employee performance at a restaurant in Bandung, researchers suggest that the company can provide all the things that can influence the variables of leadership and extrinsic motivation to provide enthusiasm, self-awareness, strong desire, and a sense of retribution for providing the best performance for the company so that it does not decrease, on the contrary, it increases every year.